Kompres NaCl 0,9% dalam Upaya Menurunkan Nyeri Post Insersi AV Fistula pada Pasien Gagal Ginjal Kronik - Isnayati Isnayati; Suhatridjas Suhatridjas (Journal of Telenursing (JOTING), 2020)
The study aimed to determine the description of the analysis of 0.9% NaCl compresses to reduce post-Fertula AV insertion pain in patients with chronic renal failure during hemodialysis. The research design is a simple descriptive research method with a case study approach, and administration of 0.9% NaCl compress therapy. The study results during the compress pain reduction occurred in the subject I and subject II; there was no allergy, both questions looked comfortable, there were no complaints of increased pain, no gestures or expressions that showed massive pain when compressed. Complaints of pain felt by the two subjects from the first hour to the fourth hour always experience a decrease in pain scale. In conclusion, there is a decrease in pain scale in question I and subject II between 2-1 every time it is compressed for four meetings. Keywords: Hemodialysis, AV Fistula Insertion, 0.9% NaCl Compress, Pain